2005
DOI: 10.1002/ffj.1426
|View full text |Cite
|
Sign up to set email alerts
|

Headspace-SPME and hydrodistillation of two fragrantArtemisia sp.

Abstract: The family Asteraceae comprises aromatic plants with a strong distinctive fragrance. Artemisia species belonging to this family are known to contain essential oils. Fresh aerial parts of Artemisia spicigera C. Koch and A. scoparia Waldst. et Kit. were subjected to headspace-SPME (HS-SPME) and the same plants were hydrodistilled (HD) after drying to obtain the profiles of volatiles. Headspace volatiles were analysed by GC-MS, whereas the essential oils were analysed by both GC and GC-MS. Camphor (37.5% and 43.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…1,8-Cineole, camphor, camphene, α-thujone, β-thujone and p-cymene were found to be the highest amounts, and between them, 1,8-cineole, camphor, and camphene were common in essential oils of the all populations. Our results are in accordance with those published by Demirci et al (2005) and Guevenalp et al (1998) that introduced 1,8-cineole, camphene and camphor as a major components of the essential oil in A. spicigera and very similar to reports of Aleskerova et al (1986) and Anonymous (2008) that demonstrated the main compounds of essential oil are camphor and 1,8-cineole, but are different from some other reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1,8-Cineole, camphor, camphene, α-thujone, β-thujone and p-cymene were found to be the highest amounts, and between them, 1,8-cineole, camphor, and camphene were common in essential oils of the all populations. Our results are in accordance with those published by Demirci et al (2005) and Guevenalp et al (1998) that introduced 1,8-cineole, camphene and camphor as a major components of the essential oil in A. spicigera and very similar to reports of Aleskerova et al (1986) and Anonymous (2008) that demonstrated the main compounds of essential oil are camphor and 1,8-cineole, but are different from some other reports.…”
Section: Discussionsupporting
confidence: 90%
“…It is an Iran-Turanian element that grows on dry slopes, steppes and rarely in salty areas with altitude about 300-2000 m (Guvenalp et al, 1998). Some researchers have reported the chemical composition of essential oils of A. spicigera (Aleskerova et al, 1986;Guevenalp, 1998;Guvenalp et al, 1998;Sefidkon et al, 2003;Kordali et al, 2005Kordali et al, , 2007Demirci et al, 2005;Rabie et al, 2006;Anon., 2008). The above mentioned studies display the different oil chemotypes, which strongly correlate with a different geographical origin, the plant material, the vegetative period, and method used for isolating the essential oils.…”
Section: Research Articlementioning
confidence: 99%
“…Moreover, the knowledge of their pattern is important to identify the compounds that have relevance in the flavour profile. In recent years, several reports have used solid-phase micro-extraction (SPME), as a novel powerful analytical technique to characterize the chemical composition of the volatiles from several species (Palá-Paúl et al 2004, Demirci et al 2005. SPME offers several advantages over dynamic headspace or hydrodistillation techniques: it is less time consuming, a non-destructive, require smaller sample sizes, and minimise the formation of artefacts (Demirci et al 2005, Flamini et al 2005.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…The most abundant volatile constituents from another Indian A. scoparia essential oil were γ-terpinene (21.8 %), eugenol (20.4 %), eugenyl valerate (5.5 %), limonene (5.0 %) and p-cymene (4.6 %) according to Ali et al 30 The major components of the essential oil from Iranian plant analyzed by Morteza-Semnani and Akbarzadeh 31 were camphor (37.9 %), 1,8-cineole (27.8 %) and borneol (21.1 %). Acenaphthene (36.86 %) was the major component of A. scoparia from India, while p-cymene (20.5 %) was the major monoterpene constituent, followed by βmyrcene (13.95 %) and (+)-limonene (12.53 %) according to Kaur et al 32 The essential oil of A. scoparia from Korea was rich in 1,8-cineole (21.5 %), camphor (11.0 %) and β-caryophyllene (6.8 %) as the major compounds according to Cha et al 33 Contrary to the above references, the composition of A. scoparia EO and HS-SPME volatiles from Turkey examined by Demirci et al 12 was very similar to the composition of A. scoparia EO and HS examined in this paper, except concerning 2,4-pentadiynyl-benzene. In here examined sample, the content of 2,4-pentadiynyl-benzene was 10.0 % in EO and 7.7 % in HS volatiles, while in the sample from Turkey it was not detected at all.…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][3] Even though headspace G-C is extensively used a limited number of papers is focused on the analysis of headspace volatiles obtained directly from the plant material under static conditions. [4][5][6][7][8][9][10][11] More papers are related to HS-SPME analysis some of which refer to A. scoparia 12 and A. annua. [13][14][15][16][17] Static headspace analysis of plants is a very fast and inexpensive method.…”
Section: Introductionmentioning
confidence: 99%